Abortos e malformações congênitas em caprinos e ratos, causados pela ingestão de Poincianella pyramidalis(Tul.) L.P. Queiroz(=Caesalpinia pyramidalis Tul.) - Souza, Maria de Fátima de Souza (2017)
Although Poincianella pyramidalis has been used therapeutically in humans, it has also been responsible for miscarriages and malformations in small ruminants, and experimental researches describing intoxication in goats, mollusks and bees have been reported, proving that the plant has toxic effects. The objective of this study was to analyze natural cases, investigate and map the cases of intoxication by P. pyramidalis in goats in the semi-arid region of the Northeast Brazil, as well as to determine the teratogenic effects in Wistar rats (Rattus novergicus) and their concepts, proving, therefore, the toxic effects of the plant. Epidemiological investigations, clinical evaluations of goats affected by malformations and necropsies of aborted fetuses were carried out in 12 properties located in the municipalities of Gurjão and Soledade - Paraíba, and one in the municipality of Pau dos Ferros - Rio Grande do Norte. The study considered only the properties that had basically the presence of P. pyramidalis among teratogenic plants. In the property located in the municipality of Pau dos Ferros, it was verified the occurrence of many abortions and birth of malformed goats, affecting 90% of pregnant goats. In the 12 properties belonging to the municipalities of Gurjão and Soledade, spontaneous cases of embryonic mortality, miscarriages and malformations affected 257 goats (41.1% of the goats of the herd). Arthrogryposis was the main congenital malformation observed. Necropsy and histopathological exams of four fetuses accompanied by placentas did not detect the presence of infectious agents. The cases of embryonic loss, abortions and malformations were predominantly concentrated during the seasons of the year when pasture was scarce, but P. pyramidalis was available on the properties due to the occurrence of pre-season rains, which did not allow the germination of pasture, but regrowth of P. pyramidalis. In the experiment using rats, 30 pregnant female Wistar rats were divided into 2 groups: experimental and control group. The experimental group was subdivided into three subgroups of five females (GI, GII and GIII), for each group were given a commercial diet with 30% of P. pyramidalis dry leaves ad libitum at different stages of gestation (1-7, 8-14, and 15-21 days). Control group received only the commercial diet ad libitum. It was decided that deliveries were normal. No differences were observed between the consumption of food and water among experimental groups and control group, nor did clinical changes occur in experimental groups. Most rats gave birth between 21-23 days. Rats from GI group had fetal reabsorption and other groups had small fetuses with bone malformation, which some of them born with congenital cataract. The results of this work demonstrate that P. pyramidalis causes problems in all stages of pregnancy, resulting in a high rate of fetal reabsorption, mortality in fetuses of goats and rats, as well as the birth of weak fetuses with morphological abnormalities.